Evaluating Fungicide Selections to Manage Pythium Root Rot on Poinsettia Cultivars with Varying Levels of Partial Resistance - Lookabaugh, Emma C (Plant disease, 2021)
Pythium aphanidermatum is the predominant species causing Pythium root rot of commercially grown poinsettia (Euphorbia pulcherrima Willd. ex Kotzch) in North Carolina. Pythium root rot is managed primarily through a combination of sanitation practices and preventative fungicide applications of mefenoxam or etridiazole. Insensitivity to mefenoxam is common but growers continue to rely on it from lack of inexpensive and efficacious alternatives. This research was conducted to identify alternative fungicides for Pythium root rot control and to evaluate their efficacy on poinsettia cultivars with varying levels of partial resistance. Greenhouse studies were conducted to assess efficacy of fungicide treatments in seven poinsettia cultivars inoculated with a mefenoxam-sensitive isolate of P. aphanidermatum. One study examined control with a single fungicide drench made at transplant and a second study examined repeat fungicide applications made throughout the experiment. Treatments containing etridiazole, mefenoxam, fenamidone, and cyazofamid provided control of Pythium root rot across all cultivars in both experiments whereas Fosetyl-al, potassium phosphite, and Trichoderma spp. failed to offer satisfactory control. Azoxystrobin, pyraclostrobin, and propamocarb reduced disease on some cultivars but failed to control Pythium root rot on highly susceptible cultivars. Four isolates of P. aphanidermatum cultured from plants growing in commercial greenhouses were evaluated for in vitro sensitivity to fungicides labeled for Pythium root rot control at four rates. Etridiazole, fosetyl-al, and potassium phosphite completely inhibited mycelial growth, whereas isolates varied in response to mefenoxam, cyazofamid, propamocarb, fenamidone, azoxystrobin, and pyraclostrobin in vitro. Twenty-one additional isolates then were evaluated at label rates of these fungicides. Seven isolates were insensitive to label rates of all three quinone outside inhibitors and one isolate was insensitive to the quinone outside inhibitors and mefenoxam. These results provide guidelines for selecting fungicides to maximize control of Pythium root rot on poinsettia cultivars